STUDI FARMAKOVIGILANS PENGOBATAN ASMA PADA PASIEN RAWAT INAP DI SUATU RUMAH SAKIT DI BOJONEGORO - Amelia Lorensia; Ratna Ayu Amalia (Jurnal Ilmiah Manuntung, 2015)
Background: Asthma is a respiratory disease with a large enough number of prevalence in the world. Asthma treatmentin hospital needs serious monitoring because of the risk to patient safety and increase the cost of treatment. One attempt to reduce the incidence of unwanted is the pharmacovigilance studies to improve patient safety.Purpose: to determine safety in terms of adverse drug reactions (ADR) and drug interactions of the treatment of inpatient asthmatic patients in a hospital.Methods: This is a non-experimental study with sampling using purposive sampling. Then the data were obtained from medical records were analyzed ADRs and drug interactions that occur using the library and shown descriptively.Results: The study sample as many as 43 people. The results showed there were 56 cases of ADRs on asthma medications, especially the use of nebulized salbutamol (57.14%). While the incidence of asthma therapy drug interactions there were 10 cases and the highest is aminophylline with salbutamol (14.29%).Conclusion: Treatment of asthma need to get to the ADR incidence and risk of drug interactions. Incidence of ADRs and drug interactions at most of the use of salbutamol which is relatively safe preference. This still needs to be done further research.